(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Praise be to Allah, the Lord of the Worlds, and prayers and peace be upon His last messenger, Prophet Mohammed, his family and companions, and those who follow his guidance until the Day of Judgment. The creation of materials related to pornography networks has become a major threat to social security, due to the risks it entails at various local and global levels, which are increasing day by day due to the development of modern technology, and have become one of the major issues that occupy the attention of the international community. In this research, the researcher tries to clarify the most important aspects related to the crime of establishing web pornographic material and their danger to society. Research Plan: To illustrate and clarify the subject of this research, the researcher divided it into an introductory topic and three topics and a conclusion. Introductory section: Explaining the most important terms contained in the study. The first Section: The causes of the crime of creating networks pornographic content, their danger to society. The second topic: The elements of the crime of creating networks pornographic content, and their danger to society in Islamic law and Arab laws. The third topic: The seriousness of the establishment of web pornographic material on the international community.